1976
DOI: 10.1111/j.1365-3083.1976.tb00308.x
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism of Migration Inhibition Involving Components of the Coagulation System

Abstract: Lymph from pigs given bacillus Calmette-Guérin (BCG) and stimulated in the drainage area of a cannulated lymph node with tuberculin (PPD) had potent in vitro macrophage migration inhibitory activity. A similar observation has previously been made in sheep by other workers. In the sheep, part of, and in the pig, almost all of, this inhibitory activity was produced, not by a factor resembling the so-called 'migration inhibitory factor', but by a mechanism involving a protease and fibrinogen. It is suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1977
1977
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Soybean trypsin inhibitor (SBTI) (100 ng/ml) but not DFP, is inhibitory for this activity; the use of fresh serum in the assay enhances its effect (55). This activity can be separated into two forms.…”
Section: E Mif In Body Fluidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Soybean trypsin inhibitor (SBTI) (100 ng/ml) but not DFP, is inhibitory for this activity; the use of fresh serum in the assay enhances its effect (55). This activity can be separated into two forms.…”
Section: E Mif In Body Fluidsmentioning
confidence: 99%
“…(iit) It has been shown that serum is required lor migration of macrophages (38,63), that the migration area of individual macropliage batches varies with individual sera used for supplementing cukure medium (6), and that LPS induces direct migration inhibition in the presence of fresh C4 deficient serum, but not in the presence of heatinactivated or zymosan-treated serum, indicating that activation of complement through the alternative pathway could have an eflect mimicking that of MIF (32). It has also been shown that high concentrations of serum (30%) in the cultures block the expression of MIF-activity (63), that the activity of ConA-induced MIF of human blood lymphocyte origin is governed by a heat sensitive (56°C for 2 h) inhibitor (CFI), which is a normal constituent of serum (84), and that fresh serum enhances part of the migration inhibitory activity of lymph from sensitized and PPD-challenged sheep (55). Thus the tiature and concentration of serum used in the culture influence the outcome of the test.…”
Section: Metkods Of Oisaymentioning
confidence: 99%
See 1 more Smart Citation
“…A similar recycling process is sometimes induced when depletion of intracellular membrane is triggered by initiation of secretion, as in the case of insulin secretion by pancreas (Orci et al, 1973). Similarly secretion of lysosomal enzymes may normally be accompanied by increased endocytosis [and this is true when certain lymphokines stimulate macrophages (Meade et al, 1974;Pantalone & Page, 1975), though it has not yet been shown with a single purified stimulant]. In such cases endocytosis compensates for exocytosis.…”
mentioning
confidence: 99%